Utilization of Energy Conversion Machines in Solar Power Systems - January Jefry Prasetya; Candra Wahyu Sportyawan; Agustine Zulaidah; Sukaryo; Sri Subekti (Universitas Muhammadiyah Palu, 2024)
The utilization of solar energy as an alternative energy source is becoming increasingly important in the face of dependence on fossil fuels and reducing greenhouse gas emissions. This study analyzes the use of various energy conversion machines in solar power systems, including photovoltaic technology, thermal solar collectors, and Stirling engines. Advances in photovoltaic technology, such as the use of perovskite materials and tandem solar cells, have improved the efficiency of converting solar energy into electricity. Innovations in thermal solar collectors, including the use of nanofluids and solar concentrator designs, have also improved the efficiency of thermal energy collection. Stirling engines show great potential in solar power systems due to their high efficiency and ability to work with a v8ariety of heat sources. This research also discusses challenges and solutions in the implementation of this technology, including initial costs, efficiency affected by weather conditions, and the importance of efficient energy storage systems. Policy support, financial incentives, and collaboration between government, industry, and research institutions are identified as key factors to accelerate the adoption of solar technology. The social and environmental impacts of solar technology implementation are significant, including reduced greenhouse gas emissions, improved energy access in remote areas, and contribution to national energy security. This research contributes to the development of renewable energy technologies and supports the transition to a more sustainable energy system.